PENGARUH RASIO SEMEN DAN PARTIKEL TERHADAP KUALITAS PAPAN SEMEN DARI LIMBAH PARTIKEL INDUSTRI PENSIL - Rizqi Putri Winanti; Luthfi Hakim; Tito Sucipto (Program studi Kehutanan USU, 2015)
Utilization of pencil shavings waste as raw material cement board is one of the alternatives to reduce timber production. The research objective was to evaluate the physical and mechanical properties of the cement board with a pencil shavings waste catalyst addition of calcium chloride on the variation ratio of materials (cement: particle: water). Cement board in this study is made of pencil shavings waste particles with various compositions of raw materials (cement: particle) 75:25; 80:20; 85:15; 90:10 with the addition of a catalyst and Calcium Chloride (CaCl2) as much as 5%. With a target density of 1.2 kg / cm2. Testing of physical and mechanical properties based on JIS 5417-1992 about cement particle board. Value of physical and mechanical properties testing of cement particle board not all fulfill with the standards of JIS A 5417-1992. The physical properties of cement particle board that fulfill with JIS A 5417-1992 standard is the density with ratio 75:25, the water content and 2 hours and 24 hours of thickness swelling . the mechanical properties of the cement particle board not fulfill with standard of JIS A 5417-1992. The best treatment is the cement board with a ratio of 90:10. The ratio of cement composition and particle pencil shavings waste no significant effect on the quality of the cement particle board produced. Keywords: cement board, CaCl2 catalyst, pencil shavings, physical and mechanical properties.